Analysis of antimicrobial consumption in a community pharmacy in 2018 (Research, Society and Development, 2020)
A medical prescription is required for dispensing antibacterials in community pharmacies, used for various types of diseases caused by bacterial agents. The objective of this research was to obtain the profile of the consumption of antibacterials sold by a community pharmacy in Teresina – PI. This was a retrospective cohort study carried out on a database of an establishment referring to the sale of antibacterials, through document analysis with content analysis. Analyzed the dispensing of antibacterials from a community pharmacy in the city of Teresina – PI, for 2018, using sales data reported to the National Controlled Products Management System (SNGPC), carried out in the Integrated Commercial System (SCI) database ). The results were shown in charts made in the Origin Pro 2016 program. In the period analyzed, the community pharmacy sold 247 antibacterials, prescribed to men (140) and women (107). The population age group that most needed the prescription was adults between 21 and 50 years old. Most of them came from private hospitals (163) and SUS hospitals (84). The concentration of sale of antimicrobials was between February and May, coincides with the rainy season in Teresina, and this climatic factor is related to the appearance of respiratory diseases. The most prescribed antibacterials were amoxicillin (38), azithromycin (28) and tobramycin (28). Based on the results, it was possible to obtain the antibacterial consumption profile of the aforementioned pharmacy and the drugs linked to respiratory diseases stand out in relation to other disease classes.